The dynamics of soil carbon in revegetated post-coal mining sites: A case study in Berau, East Kalimantan, Indonesia - WAHJUNI HARTATI; TRIYONO SUDARMADJI (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Hartati W, Sudarmadji T. 2022. The dynamics of soil carbon in revegetated post-coal mining sites: A case study in Berau, East Kalimantan, Indonesia. Biodiversitas 23: xxxx. Open pit mining practices cause the loss of vegetation cover as well as soil degradation. Post-mining land reclamation and revegetation are therefore enforced to recover the vegetation and soil quality. While several studies have revealed vegetation succession following post-mining revegetation, limited studies have focused on the carbon dynamics of the soil. This study aimed to investigate the dynamics of soil carbon stock due to mining operations and how it changed following revegetation. The research was carried out in the concession area of a coal mining company in Berau, East Kalimantan, which was divided into three sites: Sambarata Mining Operation (SMO) Site, Binungan Mining Operation (BMO) Site, and Lati Mining Operation (LMO) Site. At each site, eight research measurement plots (RMP) were established representing land with varying vegetational conditions, namely original land and post-mined lands with varying revegetation stages from open land to 12-year-old vegetation. The percentage of C content was calculated from 288 disturbed soil samples, while bulk density was analyzed from 144 whole soil samples using the Walkey & Black and gravimetric methods. We found that the C stock at the initial state after the mining operation was very low. Coal mining activities caused a loss of C in soil with an average value of 21.29%, or equal to 5.65 tons/ha. The biggest loss occurred at the SMO site (44.97%, or 13.04 tons/ha), while the smallest loss was found at the LMO site (2.24%, or 0.40 tons/ha). The carbon stock improved after revegetation, particularly in the SMO and LMO sites, and the rate of carbon stock enhancement in the soil differed across sites. The results also showed that soil carbon in the post-mining area of 10-30 cm was greater than that of the 0-10 cm layer. Along with the increasing age of plants, the vertical distribution of C stock shifted from the lower layer to the upper layer.